The Effect of Crop Seed Rate and Post Emergence Herbicide Application on Weed control and grain yield of Wheat - M. Babaei (Majallah-i ḥifāẓat-i giyāhān, 2017)
Introduction Interference weed with crop is a major concern for production in croplands particularly where modern agricultural practices such as mechanical weeding and the application of herbicides are limited. At present, the aim of weed management is to keep weed population at an acceptable level rather than to keep crop totally free of weeds. Among the weed control methods, the chemical control is the easiest one of the recent origins, as well the most successful alternative method. Materials and methods Field experiments were conducted at Shoushtar Branch, Islamic Azad University, Iran (32 0 3´ N, 480 50´ E) during winters of 2012-2013 in order to evaluate the effect of sulfosulfuron and sulfosulfuron plus metsulfuron-methyl at 30 and 45 g a.i. ha-1, respectively, and wheat seed rate at 180, 200 and 220 kg ha-1 on weed control. Experiments were carry out in a randomized complete block design with a factorial arrangement and four replicates. The plot size was 6 m × 2 m. The soil was a clay loam texture, pH 7.4 and 0.6 % organic matter content. In the experimental site, the 30-year average annual rainfall is 321.4 mm, daily average annual air temperature is minimum and maximum 9.5 °C and 46.3 °C, respectively. Wheat cv. Chamran was planted in the first fortnight of November. Seedbed preparation consisted of moldboard plowing, disking and leveling. A basal fertilizer rate of 125 kg ha-1 N (form of urea (46% N)), 75 kg ha-1 P2O5 (diammonium phosphate (18% N; 46% P2O5)), and 60 kg K2O ha-1 (sulfate of potash (50% K2O)) was applied. The whole P and K and half of N were applied at sowing. The remaining half of N was top dressed with the irrigation at the booting stage. Results and Discussion As the crop population brings competition for limited resources with the weeds, we tested different seeding rates to increase crop plant density as a measure to control weeds. The weed population was significantly affected by seed rate. In general, there was an inverse relationship between weed density (p